An Interval Analytic method for a nonlinear boundary value problem describing transport process (2010)
In recent times, the methods of interval analysis have been successfully employed to establish existence results for the solution of initial value problems. In this paper, we extend the methods to establish existence of solution for a special boundary value problem. A particular case of this problem describes equations arising in transport process